PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS BANK PADA DUAL BANKING SYSTEM DI INDONESIA - Wu, Cherrin Nathania; Indraswari, Citra Rahayu (Contemporary Studies in Economic, Finance and Banking, 2024)
The dual banking system in Indonesia still faces the problem of inadequate capitalization with a high level of leverage. This study aims to analyze the effect of capital structure on bank’s profitability in Dual Banking System in Indonesia. The data analysis method used is panel data regression and difference test on 8 conventional banks and 8 Islamic banks. Panel data regression is intended to identify the influence of capital structure proxied through DER and CAR ratios on profitability (ROA) with control variables of bank size and asset’s growth. The secondary data used is annual report data for the period 2013-2022 sourced from OJK. The estimation results on conventional banking show that the DER and growth variable has a significant positive impact on profitability, while CAR and bank size have no significant influence on profitability. Then, in Islamic banking, DER has a significant negative influence on profitability performance, while CAR and growth have no significant influence on Islamic bank’s profitability performance. Meanwhile, bank size is proven to affect the Islamic bank’s profitability performance. Through a t-test, there is a significant difference in profitability performance and capital structure between the two banking systems in Indonesia.